PEMANFAATAN SISTEM RESI GUDANG DI CV TRIANOM AGROTEKTUR (KADATUAN KOFFIE) DENGAN IKATAN KELOMPOK TANI - Achmad Andriyanto; Hilman Setiadi; Gayuh Minang Lati; Mubassiran Mubassiran (LPPM Politeknik Pos Indonesia, 2023)
Coffee farmers are still often faced with the problem of unstable coffee selling prices during the harvest season to a price level that is not profitable for farmers. This problem often occurs in almost all agricultural commodity producers. Meanwhile, agricultural commodities themselves are very vulnerable to price fluctuations where during the main harvest the price will fall, while during a famine, prices will soar. One way to overcome this problem is to delay the sale of their crops, but farmers will need money in cash to finance their daily needs. One alternative way to deal with the various losses incurred by farmers due to the drop in coffee prices is to implement a warehouse receipt system. The Warehouse Receipt System (SRG) is a system innovation created by the Ministry of Trade (Kemendag). This WRS aims to overcome various problems that occur during the harvest season. The main problem that often occurs when the harvest season arrives is the decline in commodity prices. This will certainly be detrimental to both farmers. When using SRG, farmers will feel the benefits. Utilization of WRS that will be obtained by farmers is the profit from the difference in selling prices obtained during harvest and post-harvest. The benefits of this WRS will be obtained by the availability of facilities and infrastructure in the warehouse. However, not all farmers are willing to use this WRS. Therefore, in implementing WRS, it is necessary to provide training in the form of outreach, education, and success stories to farmers and institutions such as cooperatives to accommodate their crops. Based on the results of the implementation of community service entitled